ASSESSING THE EXTENT OF INDUCED LEAKAGE TO AN URBAN AQUIFER USING ENVIRONMENTAL TRACERS: AN EXAMPLE FROM BISHKEK, CAPITAL OF KYRGYZSTAN, CENTRAL ASIA - Morris B.L.; Darling W.G.; Gooddy D.C.; Neumann I.; Litvak R.G.; Nemaltseva E.J.; Poddubnaia I. (My University, 2006)
A groundwater residence time study of the deep fluvioglacial aquifer supplying Bishkek, capital of Kyrgyzstan, has found evidence of deep infiltration of recent recharge both in the main periurban wellfield and below the city. Commonly-employed hydrochemical markers detected urban influence in the city-centre to depths of 65-100 m, but gave no indication of the important role of induced river/canal bed leakage, either upgradient in the periurban wellfield or within the city. This was revealed by O and H stable isotope measurements, which showed that local rainfall/snowfall play little part in the aquifer water balance. More remarkably, the universal detection of CFCs and SF6, including in boreholes with 140-220 m deep upper screens, demonstrated that induced leakage of water just a few decades old had penetrated much deeper into the aquifer system than other hydrochemical markers indicated. A two-dimensional flow model set up to test whether such deep pumping-induced leakage could occur below the periurban wellfield confirmed its feasibility. The results imply vertical infiltration rates of 5-10 m/year and demonstrate that in this not-uncommon intergranular aquifer setting, deep boreholes with deep screen settings do not necessarily abstract old water. Hence, there are major implications for urban groundwater management and protection in such settings. © British Geological Survey 2005.
Keywords: CENTRAL ASIA; CFCS; GROUNDWATER AGE; GROUNDWATER MANAGEMENT; GROUNDWATER RECHARGE/WATER BUDGET; KYRGYZSTAN; STABLE ISOTOPES; URBAN GROUNDWATER